Die Entdeckung des AV-Knotens des Herzens durch Sunao Tawara und Ludwig Aschoff - Aumüller, Gerhard (DMW - Deutsche Medizinische Wochenschrift, 2019)
Already in 1664, the Danish anatomist and naturalist Niels Stensen proved that the heart is a muscle. But for a long time it remained unclear what triggered the heart contractions.The Dutch physiologist Willem Einthoven registered the electrical processes in the contraction of the heart muscle and thus provided the first electrophysiological basis of cardiac muscle activity. Since 1903, Sunao Tawara was assistant to Ludwig Aschoff in Marburg. Both left Marburg in 1906: Tawara went back to Japan and Aschoff to Freiburg. In 1905, Tawara discovered the connections of the His’ bundle to the AV node and the Purkinje fibers. At that time, there was no thought of a functional interpretation. Tawara discovered a kind of “knot” that linked to the adjacent myocardial cells, as well as the “Tawara thighs”, which frayed and went into structures known as Purkinje fibers. Tawara detected the tree-like structure he had discovered as a muscle-fiber system that controlled the arousal of the heart’s musculature. Thus the old dispute between myogenic and neurogenic arousal of the heart was decided in favor of the myogenic excitation conduction. The atrioventricular node described by Tawara was given the eponym “Aschoff-Tawara node”. Tawara’s groundbreaking work on the conduction system was the basis for the discovery of the sinus node and the interpretation of the heart’s electrophysiology.
Keywords: Elektrophysiologie; Brückenfasern; Atrioventrikularbündel; Zusammenarbeit; Marburg